IPTEKS BALANCED SCORECARD PADA PT. DAYA ANUGRAH MANDIRI MANADO - Kawatu, Brenda M L; Tamaka, Nadiya R; Latjandu, Lady D (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
One important factor in assessing the achievements and success of a company to achieve a company goal is by conducting a performance appraisal analysis, PT Daya Anugrah Mandiri Manado is a company engaged in the sale of Honda motorcycles and maintenance which of course must be carried out performance assessment to measure level of achievement and success achieved. In this study the author conducted an analysis on PT Daya Anugrah Mandiri Manado for performance assessment using the Balanced Scorecard method which discusses several things in the method. With the method of performance assessment analysis and financial perspective techniques, customer perspective, internal business process perspective, learning and growth perspective. The results of the study are very good at using this method to assess the growth performance of the company. With suggestions, you can do an analysis of PT Daya Anugrah Mandiri Manado in order to find out whether there is performance growth or not.Keywords : performance measurement, balanced scorecard